SEARCH FOR GLIOMA DIRECT BINDING SITE OF ALKALOID USING PROTEIN-LIGAND ANT SYSTEM® - Rifai, Yusnita (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This research aims to know the best affinity and the best chemical conformation of anticancer compounds from alkaloid groups that have closed direction to Glioma-associated oncogene using protein-ligand ant system (PLANTS®). The interaction energy and hydrogen bond are included as evaluated targets. Methods: In this research, 27 ligands with root mean square deviation score at 1.614 Å and cyclopamine as native ligand are used. Meanwhile, staurosporinone acts as gliomas directed-binding-site-internal-control. Each ligand is docked in GLI with Protein Data Bank code 2GLI using two methods, GLI contains water and without water. Results: PLANTS® score for native ligand in the first and the second method is −73.9002 and −73.2700, respectively. Pancracristine, homoharringtonine, and sanguinarine showed PLANTS® score closed to the cyclopamine score result, but their hydrogen bond interaction differed from native ligan interaction. Evodiamine ligand has a good score and hydrogen bond to the same amino acid of protein GLI, which are GLU 175 and THR 173. This result indicated that evodiamine has the same identical mechanism as staurosporinone. Conclusion: The evodiamine is determined to have the same working mechanism as a GLI inhibitor.